Modernization of the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) Program: Rationale and Overview of the THIS-WIC (Telehealth Intervention Strategies for WIC) Project - Catherine Wright; Pascasie Adedze; Alice Ammerman; Lauren Au; Alan Barnosky; Jonathan Blitstein; Karen Castellanos-Brown; Sheryl Cates; Madhur Chandra; Kenneth Kwan Ho Chui; Katharine Clarke; Christina Economos; et al. (Journal of Nutrition Education and Behavior, 2026)

Elevated levels of circulating plasma sPDGFRβ in cognitively impaired APOE4 carriers - Abhay P. Sagare; Trevor Lohman; Ivan Ramirez; Elizabeth B. Joe; Michael G. Harrington; Helena C. Chui; Lon S. Schneider; Hussein N. Yassine; John M. Ringman; Arthur W. Toga; Daniel A. Nation; Berislav V. Zlokovic (GeroScience, 2026)
Increased levels of cerebrospinal fluid (CSF) soluble platelet-derived growth factor receptor-β (sPDGFRβ), a marker of blood–brain barrier (BBB)-associated pericyte cell injury, have been shown to correlate with increased BBB permeability and severity of Alzheimer’s disease (AD) pathology. It has been also shown that increased CSF sPDGFRβ levels can predict cognitive dysfunction in APOE4 carriers bearing the main susceptibility gene for AD. Whether plasma sPDGFRβ levels are also elevated in APOE4 carriers has not been explored. Here, we analyzed plasma samples for sPDGFRβ levels, Ab 42/40 ratio, and pTau217 in 115 APOE3 homozygotes and APOE4 carriers with Clinical Dementia Rating (CDR) score of 0 and 0.5. Our data show that plasma sPDGFRβ levels are increased in APOE4 carriers with cognitive impairment compared to APOE4 carriers that are cognitively unimpaired as well as relative to cognitively impaired APOE3 carriers even after controlling for plasma Aβ 42/40 ratio and pTau217. Thus, our data suggest that plasma sPDGFRβ is a useful biomarker of brain pericytes/BBB damage in APOE4 carriers.

Association between late-life air pollution exposure and medial temporal lobe atrophy in older women - Xinhui Wang; Lauren E. Salminen; Andrew J. Petkus; Ira Frahmand; Joshua Millstein; Daniel P. Beavers; Mark A. Espeland; Guray Erus; Meredith N. Braskie; Paul M. Thompson; Margaret Gatz; Helena C. Chui; et al. (NeuroToxicology, 2026)

Cerebral hypoperfusion, brain structural integrity, and cognitive impairment in older APOE4 carriers - Ioannis Pappas; Trevor Lohman; Shubir Dutt; Arunima Kapoor; Allison C. Engstrom; John Paul M. Alitin; Samuel Barnes; Ararat Chakhoyan; Lucas Saca; Raghav Gaggar; Elnaz Nourollahimoghadam; Danny J. J. Wang; et al. (GeroScience, 2025)
Cerebral blood flow (CBF) deficits, cognitive decline, and brain structural changes have been reported in older adults with and without apolipoprotein E-e4 ( APOE4 )-related risk for dementia. However, it remains unclear whether brain structural changes mediate the effects of hypoperfusion on cognitive impairment in APOE4 carriers and non-carriers. We studied 166 (60–89 years) APOE4 carriers (ε3/ε4 or ε4/ε4) and APOE3 homozygotes (e3/e3) with and without cognitive impairment by clinical dementia rating (CDR) and neuropsychological testing. Pseudocontinuous arterial spin-labeling-MRI assessed regional CBF, and T1-anatomical and diffusion-MRI assessed structural integrity. Mediation analyses examined relationships among grey matter CBF, grey matter volume, and white matter integrity in regions underlying impairment in distinct cognitive ability domains. APOE4 carriers with global/memory impairment (CDR 0.5) exhibited decreased CBF in the posterior cingulate, decreased grey matter volume in the hippocampus, parahippocampal gyrus, and posterior cingulate, and decreased white matter integrity in the cingulum relative to APOE4 carriers with no impairment (CDR 0). Mediation analysis in APOE4 carriers indicated decreased posterior cingulate CBF effects on global/memory impairment were mediated by decreased cingulum integrity. In the combined APOE4 and APOE3 carriers sample, there were direct effects of frontal and inferior parietal CBF and superior longitudinal fasciculus integrity on attention/executive impairment. There were also direct effects of left inferior frontal CBF on language impairment. Findings suggest links between hypoperfusion and brain structural integrity underlying global/memory impairment in APOE4 carriers. Independent CBF relationships with structural integrity are also identified across genotypes and impairment domains.

ADHD/CD-NET: automated EEG-based characterization of ADHD and CD using explainable deep neural network technique - Hui Wen Loh; Chui Ping Ooi; Shu Lih Oh; Prabal Datta Barua; Yi Ren Tan; U. Rajendra Acharya; Daniel Shuen Sheng Fung (Cognitive Neurodynamics, 2024)
In this study, attention deficit hyperactivity disorder (ADHD), a childhood neurodevelopmental disorder, is being studied alongside its comorbidity, conduct disorder (CD), a behavioral disorder. Because ADHD and CD share commonalities, distinguishing them is difficult, thus increasing the risk of misdiagnosis. It is crucial that these two conditions are not mistakenly identified as the same because the treatment plan varies depending on whether the patient has CD or ADHD. Hence, this study proposes an electroencephalogram (EEG)-based deep learning system known as ADHD/CD-NET that is capable of objectively distinguishing ADHD, ADHD + CD, and CD. The 12-channel EEG signals were first segmented and converted into channel-wise continuous wavelet transform (CWT) correlation matrices. The resulting matrices were then used to train the convolutional neural network (CNN) model, and the model’s performance was evaluated using 10-fold cross-validation. Gradient-weighted class activation mapping (Grad-CAM) was also used to provide explanations for the prediction result made by the ‘black box’ CNN model. Internal private dataset (45 ADHD, 62 ADHD + CD and 16 CD) and external public dataset (61 ADHD and 60 healthy controls) were used to evaluate ADHD/CD-NET. As a result, ADHD/CD-NET achieved classification accuracy, sensitivity, specificity, and precision of 93.70%, 90.83%, 95.35% and 91.85% for the internal evaluation, and 98.19%, 98.36%, 98.03% and 98.06% for the external evaluation. Grad-CAM also identified significant channels that contributed to the diagnosis outcome. Therefore, ADHD/CD-NET can perform temporal localization and choose significant EEG channels for diagnosis, thus providing objective analysis for mental health professionals and clinicians to consider when making a diagnosis.

In-Silico Modelling of Transdermal Delivery of Macromolecule Drugs Assisted by a Skin Stretching Hypobaric Device - Daniel Sebastia-Saez; Faiza Benaouda; Chui Hua Lim; Guoping Lian; Stuart A. Jones; Liang Cui; Tao Chen (Pharmaceutical Research, 2023)
Objectives To develop a simulation model to explore the interplay between mechanical stretch and diffusion of large molecules into the skin under locally applied hypobaric pressure, a novel penetration enhancement method. Methods Finite element method was used to model the skin mechanical deformation and molecular diffusion processes, with validation against in-vitro transdermal permeation experiments. Simulations and experimental data were used together to investigate the transdermal permeation of large molecules under local hypobaric pressure. Results Mechanical simulations resulted in skin stretching and thinning (20%–26% hair follicle diameter increase, and 21%–27% skin thickness reduction). Concentration of dextrans in the stratum corneum was below detection limit with and without hypobaric pressure. Concentrations in viable epidermis and dermis were not affected by hypobaric pressure (approximately 2 μg $$\bullet$$ ∙ cm −2 ). Permeation into the receptor fluid was substantially enhanced from below the detection limit at atmospheric pressure to up to 6 μg $$\bullet$$ ∙ cm −2 under hypobaric pressure. The in-silico simulations compared satisfactorily with the experimental results at atmospheric conditions. Under hypobaric pressure, satisfactory comparison was attained when the diffusion coefficients of dextrans in the skin layers were increased from $$\sim$$ ∼ 10 μm 2 $$\bullet$$ ∙ s −1 to between 200–500 μm 2 $$\bullet$$ ∙ s −1 . Conclusions Application of hypobaric pressure induces skin mechanical stretching and enlarges the hair follicle. This enlargement alone cannot satisfactorily explain the increased transdermal permeation into the receptor fluid under hypobaric pressure. The results from the in-silico simulations suggest that the application of hypobaric pressure increases diffusion in the skin, which leads to improved overall transdermal permeation.

Individual identification and photographic techniques in mammalian ecological and behavioural research—Part 1: Methods and concepts - Leszek Karczmarski; Stephen C. Y. Chan; Daniel I. Rubenstein; Scott Y. S. Chui; Elissa Z. Cameron (Mammalian Biology, 2022)

A prospective comparative study of children with gastroenteritis: emergency department compared with symptomatic care at home - Otto G. Vanderkooi; Jianling Xie; Bonita E. Lee; Xiao-Li Pang; Linda Chui; Daniel C. Payne; Judy MacDonald; Samina Ali; Shannon MacDonald; Steve Drews; Lara Osterreicher; Kelly Kim; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Knockout of MCT1 results in total absence of spermatozoa, sex hormones dysregulation, and morphological alterations in the testicular tissue - Raquel L. Bernardino; Warren N. D’Souza; Luis Rato; Jay L. Rothstein; Tânia R. Dias; Daniel Chui; Sharon Wannberg; Marco G. Alves; Pedro F. Oliveira (Cell and Tissue Research, 2019)